Understanding the backward classes of Muslim society - Krishnan, P.S. (2010)
The identification of and reservation for the backward classes among Muslims has been a contentious issue, most recently in Andhra Pradesh. However there is a clear case, on constitutional grounds, for such reservation. A detailed discussion of the national situation and reservation measures in some states. - Reproduced.
Keywords: Backward classes